2017
DOI: 10.3892/ol.2017.7355
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between chemotherapy resistance in osteosarcoma patients and PAK5 and Ezrin gene expression

Abstract: The correlation between PAK5 (P21-activated kinase 5) and Ezrin gene expression and chemotherapy resistance of osteosarcoma patients was investigated. The cisplatin (CDDP)-resistance model of osteosarcoma cells SOSP-9607/CDDP was established to detect the cell growth curve. Methyl thiazolyl tetrazolium (MTT) assay was used to detect the drug resistance of cells to chemotherapy drugs. Transwell assay was used to detect the invasive capacity of cells. Semi-quantitative PCR (qPCR) was used to detect the mRNA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Multiple markers of tumor aggressiveness have been identified in exploratory studies, and while not prospectively validated may provide insight into the biology of these tumors. In osteosarcoma mouse models, ezrin was associated with increased metastatic potential and poorer prognosis while high ezrin expression correlated with chemotherapy resistance (6,17). Over-expression of MTA-1 has been noted in high-grade osteosarcoma tumor samples with little to no expression in low-grade samples (9).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple markers of tumor aggressiveness have been identified in exploratory studies, and while not prospectively validated may provide insight into the biology of these tumors. In osteosarcoma mouse models, ezrin was associated with increased metastatic potential and poorer prognosis while high ezrin expression correlated with chemotherapy resistance (6,17). Over-expression of MTA-1 has been noted in high-grade osteosarcoma tumor samples with little to no expression in low-grade samples (9).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ezrin deletion in autophagic TAMs decreased TGF-β1 expression and contributed to EMT as well as the cell migration and invasion ability of lung adenocarcinomas. Ezrin, an important regulatory protein that connects cell membrane molecules, is highly expressed in various solid tumors and is associated with poor prognosis (35,36). Chen et al reported that ezrin can mediate EMT in A549 cells through the TGF-β1 pathway (37).…”
Section: Discussionmentioning
confidence: 99%
“…Statistical significance was considered as p ≤ 0.05. Further, for correlations between Mthfr and genes involved in hepatic lipid metabolism, Pearson’s correlation coefficient was computed [ 12 ].…”
Section: Methodsmentioning
confidence: 99%